Prevalensi katarak pada anak di RSUP H. Adam Malik Medan tahun 2012 - Iridha Wahyumi; Zaldi dr; Aryani A Amra (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Introduction : A cataract is a cloudiness that occurs in the lens of the eye , which in normal conditions clear.Objective : To obtain the prevalence of cataract in children in hospital . H. Adam Malik Medan in 2012.Methods : This was a retrospective descriptive study . Data obtained from medical records of patients who were suffering from cataracts who went to the ophthalmology clinic of children RS H Adam Malik Medan in 2012 .Results : The age group of 4-6 years is the group (24.4%) age of majority , while the smallest age group 13-17 years ( 13.3%). Cataracts in children more dominating in boys is equal to 57.8% of girls. Based on the most lateralitas be unilateral , ie 64.4%, with the involvement of the right eye the most experienced , when compared with the left eye. While 35.6% occurred in children with bilateral cataracts . Nontraumatic cataract occurs at 53.3% . While traumatic cataract which was only 46.7% . Of the number of patients with cataract in children by 45 people, then the prevalence of cataract in children in RS Adam Malik in 2012 amounted to 0.55% .Conclusion : The prevalence of cataract in children in RS Adam Malik Medan in 2012 is 0.55% . Which can be used as a reference for the prevention and treatment of cataracts .Keywords : cataract in children; cataracts; nontraumatic cataract; traumatic cataract